Suits. Season two [videorecording (DVD)] - Torres, Gina; Macht, Gabriel, 1972-; Adams, Patrick J., 1981- (Universal Studios Home Entertainment, 2013)
Mike and Harvey must keep their secret from everyone including managing partner Jessica as they take on New York's most high profile cases.